2014
DOI: 10.1155/2014/376754
|View full text |Cite
|
Sign up to set email alerts
|

New Semi-IPN Hydrogels Based on Cellulose for Biomedical Application

Abstract: Cellulose pulp, obtained from a paper industry, has been dissolved in PEG/NaOH system and the resulting solution has been polymerized in the presence of monomer acrylic acid (AA) and crosslinker N,N′ methylene bisacrylamide via free radical polymerization. The Cell/PEG/poly (SA) ternary semi-IPN hydrogel, so prepared, was characterized by FTIR and TG analysis. The dynamic water uptake of various hydrogels, having different compositions, was investigated in the physiological buffer of pH 7.4 at 37°C. The variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(30 reference statements)
0
4
0
1
Order By: Relevance
“…Cellulose has found particular favor in biomedical sciences due to its mechanical strength, biocompatibility, and hydrophilicity, making it a promising polysaccharide for the production of biocompatible porous cryogels [10][11][12]. Cellulose-based materials have been proposed for a variety of biomedical applications [13,14] because, unlike other polysaccharides, cellulose is relatively bioinert and is not biodegraded in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose has found particular favor in biomedical sciences due to its mechanical strength, biocompatibility, and hydrophilicity, making it a promising polysaccharide for the production of biocompatible porous cryogels [10][11][12]. Cellulose-based materials have been proposed for a variety of biomedical applications [13,14] because, unlike other polysaccharides, cellulose is relatively bioinert and is not biodegraded in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Erizel 30 prepared starch–poly(acrylamide-co-acrylic acid) hydrogels by gamma radiations and found that GF decreased with starch contents. However, the opposite trend was observed in the case of radiation-induced CMC/acrylamide co-polymeric hydrogels, 31 where the CMC content of 2%, 3%, and 5% showed GF values of 0.30, 0.55, and 0.65, respectively. We also determined GF of semi-IPNs having varying amounts of cross-linking agents (i.e.…”
Section: Resultsmentioning
confidence: 87%
“…In a recent work, 38 superabsorbent hydrogels, consisting of CMC-g-poly(acrylic acid-co-acrylamido-2-methylpropanesulfonic acid), have demonstrated k 2 values in the order of 10 −2 (g/g min) −1 . Most recently, we 31 reported values of k 2 in the range of 0.228–3.88 × 10 −3 (g/g min) −1 for cellulose/poly(sodium acrylate) semi-IPNs. It is also clear from the data shown in Table 2 that the theoretical and experimental ESR do not show fair agreement and ESR (theo) is greater than ESR (exp) .…”
Section: Swelling Behavior Of Semi-ipn Samplesmentioning
confidence: 99%
“…Además, deben tener la capacidad de liberar sustancias terapéuticas de forma controlada y poseer alta biocompatibilidad 8 . Una estrategia para la obtención de estos materiales es la formación de matrices de redes poliméricas semi-interpenetradas (semi-IPN) a base de polímeros naturales y sintéticos 9 . Los polímeros naturales como el colágeno y los polisacáridos como la pectina permiten mantener y regular la biocompatibilidad de los hidrogeles 10,11 .…”
Section: Introductionunclassified